Responsabilidad social empresarial y longevidad. El caso de microempresas del sector comercial en Palenque y Catazajá, Chiapas (2021)
Social responsibility today involves collaboration between communities and companies, which entails a clear awareness that actions today will have an impact on the future and, in this sense, that corporate social responsibility (csr) is responsible for the well-being of company, community and environment. This study found that, overall, microenterprises in Palenque and Catazajá (n=95) do comply with the three main aspects of corporate social responsibility, with a good balance between the social (3.77), the economic (3.70), and the environmental (3.87). Just under half of the companies (n=40) have been implementing some of these strategies for 10 years, which “supports” the notion that csr contributes to their longevity.